Liquidity and stock returns in order driven Asian markets : evidence from the Singapore stock market - Ang, Andy Seng Chong (2008)
We study the relationship between liquidity and stock returns in the pure order driven Singapore stock exchange using the Restricted Seemingly Unrelated Regression (SURE). The aim of the study is to determine if a liquidity premium exists. The adjusted bid-ask spread and adjusted turnover are used as proxies for liquidity.